Architectural Pattern of the Team Emergency Service Model as a Health Service Management Strategy in Wakatobi District - EDI HASAN; M. NATSIR; MUHAMMAD NASIR; SYAMSIR; MUHAMMAD WAJDI (International Journal of Multidisciplinary Research and Studies, 2023)
Public services in the health sector are the responsibility of the government so that efforts to improve services and improvements through health service innovation are continuously carried out. At present, due to advances in science and technology, it also encourages the emergence of ideas and the implementation of community interaction by monitoring and controlling various existing community resources by means of technology. One of them is the concept of development and management using Information and Communication Technology (ICT) in the health sector. One of them is an effort to differentiate the emergency service model in the form of an emergency service team program.Next, it is necessary to identify innovative alternative architectural patterns for the emergency service team model that is adaptable and characterizes health services with appropriate geographical conditions and population topography and reaches all sides of the Wakatobi district area so that its implementation can be utilized and become an alternative that answers community complaints about services, especially emergency services. The aim of this research is to find out the architectural pattern of the emergency service team model that can be applied to health service settings in Wakatobi Regency. The research design used was qualitative, with analysis using the PIECES and TELOS methods which was carried out on 12-16 June 2023 with a sample of 15 people. The research results show the existence of emergency services through the implementation of team emergency service innovation as a health service management strategy with new value attributes in the form of one-stop integrated services (One Stop Service), in the form of work teams (interprofessional collaboration/IPC), shortening service time (Respontime) and adaptation sophisticated technology in its application by considering the appropriate topography of the Wakatobi region is the architectural pattern of the convergence model which is a combination of simultaneous and parallel models.